2009
DOI: 10.1111/j.1438-8677.2009.00261.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic‐dependent changes in plant cell redox power after ozone exposure

Abstract: The tropospheric level of the phytotoxic air pollutant ozone has increased considerably during the last century, and is expected to continue to rise. Long-term exposure of higher plants to low ozone concentrations affects biochemical processes prior to any visible symptoms of injury. The current critical level of ozone used to determine the threshold for damaging plants (biomass loss) is still based on the seasonal sum of the external concentration above 40 nl.l(-1) (AOT40). Taking into account stomatal conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 80 publications
4
64
0
1
Order By: Relevance
“…Depending on the duration and intensity of the exposure, O 3 can induce a range of responses that are typically deleterious to plant fitness, disturbing photosynthetic processes, energy and carbon metabolism, cellular detoxification, and transpiration Dizengremel et al, 2008;Fares et al, 2010;Goumenaki et al, 2010;Salvatori et al, 2015). While acute exposure to high O 3 levels can rapidly induce cell death and chlorosis (Ashmore, 2005;Kangasjärvi et al, 2005;Vainonen and Kangasjärvi, 2015), negative yield responses are not always correlated with the severity of symptoms in leaves, and exposure to O 3 can affect metabolic processes before any visible injury (Long and Naidu, 2002;Dizengremel et al, 2009;Sawada and Kohno, 2009;Pinto et al, 2010).…”
mentioning
confidence: 99%
“…Depending on the duration and intensity of the exposure, O 3 can induce a range of responses that are typically deleterious to plant fitness, disturbing photosynthetic processes, energy and carbon metabolism, cellular detoxification, and transpiration Dizengremel et al, 2008;Fares et al, 2010;Goumenaki et al, 2010;Salvatori et al, 2015). While acute exposure to high O 3 levels can rapidly induce cell death and chlorosis (Ashmore, 2005;Kangasjärvi et al, 2005;Vainonen and Kangasjärvi, 2015), negative yield responses are not always correlated with the severity of symptoms in leaves, and exposure to O 3 can affect metabolic processes before any visible injury (Long and Naidu, 2002;Dizengremel et al, 2009;Sawada and Kohno, 2009;Pinto et al, 2010).…”
mentioning
confidence: 99%
“…During the hottest seasons of the year, the respiratory rates of the plants are higher and can also induce an increasing antioxidant response due to a consequent higher ROS production in mitochondria. This respiratory increase is associated with an increase in the NADH synthesis (Dizengremel et al, 2009), which is related to the production of enzymes such as SOD. For example, Zhang et al (2008) found a significant copperzinc SOD increase in Elsholtzia haichowensis during the enhancement of respiration rates induced by some stress factors.…”
Section: Resultsmentioning
confidence: 99%
“…The sensitivity of plants to O 3 has been linked to O 3 flux controlled by stomata (Dizengremel et al, 2009;Fiscus et al, 2005) and antioxidant capacity determined by antioxidant pools and enzymes (Biswas et al, 2008;Feng et al, 2010;Inada et al, 2012;Li et al, 2016;Wang et al, 2014aWang et al, , 2014b. However, there was no significant interaction between cultivar and O 3 in g s across the four measurements (Table 1, a a a a a a Fig.…”
Section: Discussionmentioning
confidence: 97%